Clinical outcome of posterior-stabilized total knee arthroplasty using an increased flexion gap in patients with preoperative stiffness. (April 2020) - Boettner, Friedrich; Sculco, Peter; Faschingbauer, Martin; Rueckl, Kilian; Windhager, Reinhard; Kasparek, Maximilian F.
Abstract : Aims: To compare patients undergoing total knee arthroplasty (TKA) with ≤ 80° range of movement (ROM) operated with a 2 mm increase in the flexion gap with matched non-stiff patients with at least 100° of preoperative ROM and balanced flexion and extension gaps. Methods: In a retrospective cohort study, 98 TKAs (91 patients) with a preoperative ROM of ≤ 80° were examined. Mean follow-up time was 53 months (24 to 112). All TKAs in stiff knees were performed with a 2 mm increased flexion gap. Data were compared to a matched control group of 98 TKAs (86 patients) with a mean follow-up of 43 months (24 to 89). Knees in the control group had a preoperative ROM of at least 100° and balanced flexion and extension gaps. In all stiff and non-stiff knees posterior stabilized (PS) TKAs with patellar resurfacing in combination with adequate soft tissue balancing were used. Results: Overall mean ROM in stiff knees increased preoperatively from 67° (0° to 80°) to 114° postoperatively (65° to 135°) (p < 0.001). Mean knee flexion improved from 82° (0° to 110°) to 115° (65° to 135°) and mean flexion contracture decreased from 14° (0° to 50°) to 1° (0° to 10°) (p < 0.001). The mean Knee Society Score (KSS) improved from 34 (0 to 71) to 88 (38 to 100) (p < 0.001) and the KSS Functional Score from 43 (0 to 70) to 86 (0 to 100). Seven knees (7%) required manipulations under anaesthesia (MUA) and none of the knees had flexion instability. The mean overall ROM in the control group improved from 117° (100° to 140°) to 123° (100° to 130°) (p < 0.001). Mean knee flexion improved from 119° (100° to 140°) to 123° (100° to 130°) (p < 0.001) and mean flexion contracture decreased from 2° (0° to 15°) to 0° (0° to 5°) (p < 0.001). None of the knees in the control group had flexion instability or required MUA. The mean KSS Knee Score improved from 48 (0 to 80) to 94 (79 to 100) (p < 0.001) and the KSS Functional Score from 52 (5 to 100) to 95 (60 to 100) (p < 0.001). Mean improvement in ROM (p < 0.001) and KSS Knee Score (p = 0.017) were greater in knees with preoperative stiffness compared with the control group, but the KSS Functional Score improvement was comparable (p = 0.885). Conclusion: TKA with a 2 mm increased flexion gap provided a significant improvement of ROM in knees with preoperative stiffness. While the improvement in ROM was greater, the absolute postoperative ROM was less than in matched non-stiff knees. PS TKA with patellar resurfacing and a 2 mm increased flexion gap, in combination with adequate soft tissue balancing, provides excellent ROM and knee function when stiffness of the knee had been present preoperatively. Cite this article: Bone Joint J 2020;102-B(4):426–433.